Evolutionary priority effects persist in anthropogenically created habitats, but not through nonnative plant invasion. Issue 2 (13th April 2017) - Brandt, Angela J.; Lee, William G.; Tanentzap, Andrew J.; Hayman, Ella; Fukami, Tadashi; Anderson, Barbara J.
Summary: Evolutionary priority effects, where early‐arriving lineages occupy niche space via diversification and preclude dominance of later arrivals, have been observed in alpine and forest communities. However, the potential for evolutionary priority effects to persist in an era of rapid global change remains unclear. Here, we use a natural experiment of historical disturbance in New Zealand to test whether anthropogenic changes in available habitat and nonnative invasion eliminate the role of evolutionary priority effects in community assembly. We also test whether evolutionary priority effects diminish with decreasing resource availability. Older plant clades, as estimated by clade crown age, were relatively more abundant in both primary and secondary grassland. Relative abundance in primary grassland decreased with clade stem age, but only weakly. However, for both clade age estimates, relative abundance decreased with age when nonnative biomass was high and soil moisture was low. Our data show that patterns in community structure consistent with evolutionary priority effects can occur in both primary and secondary grasslands, the latter created by anthropogenic disturbance. However, nonnative invasion may overwhelm the effect of immigration timing on community dominance, possibly as a result of high immigration rates and preadaptation to anthropogenically modified environments.